EXTH-37. PAK4 INHIBITION REPROGRAMS VASCULAR MICROENVIRONMENT AND IMPROVES CAR T IMMUNOTHERAPY IN GLIOBLASTOMA. (12th November 2021) - Yang, Fan; Binder, Zev; O'Rourke, Donald M; Fan, Yi
Abstract: Malignant solid tumors are characterized by aberrant vascularity that inhibits T cell adhesion to vasculature and impedes T cell delivery into the tumors, contributing to glioblastoma (GBM) resistance to T cell-based immunotherapy such as adoptive chimeric antigen receptor (CAR)–T transfer. Vascular abnormality is driven by pro-angiogenic pathway activation and genetic reprogramming in tumor endothelial cells (ECs). Here, our kinome-wide functional screening of mesenchymal-like transcriptional activation in human GBM-derived ECs identifies p21-activated kinase 4 (PAK4) as a selective regulator of genetic programming and aberrant vascularization in tumor. Genetic ablation of PAK4 reprograms EC transcriptome and inhibits mesenchymal-like transformation. Interestingly, deficiency of PAK4 induces adhesion protein re-expression in tumor ECs, reduces vascular abnormalities in tumors, improves T cell infiltration into the tumors, and inhibits GBM growth in mice. Moreover, pharmacological PAK4 inhibition normalizes the tumor vascular microenvironment and sensitizes GBM to Egfrviii CAR–T cell immunotherapy. Finally, we reveal a MEF2D/ZEB1- and SLUG-mediated mechanism by which PAK4 reprograms the EC transcriptome and downregulates claudin-14 and VCAM-1 expression, enhancing vessel permeability and reducing T cell adhesion to the endothelium. Thus, targeting PAK4-mediated EC plasticity may offer exciting opportunities to recondition the vascular microenvironment and strengthen cancer immunotherapy.